Historical Perspective of Proactive and Reactive Regulations of E-cigarettes to Combat Nicotine Addiction. Issue 6 (December 2020) - Gholap, Vinit; Halquist, Matthew S.
Abstract : Abstract: Cigarettes and electronic cigarettes (e-cigarettes) are major sources of exposure to nicotine, an addictive chemical. Although these products are being regulated by the Food and Drug Administration (FDA) under the Tobacco Control Act, specifications about the nicotine content in these products have not been established yet. In e-cigarettes, nicotine concentration ranges from 0 to > 50mg/mL, and the recent e-cigarette devices provide control to change nicotine flux for higher nicotine delivery. Due to the lack of robust regulations in manufacturing, distribution and marketing, e-cigarettes have already infiltrated the market with youth appealing flavors and devices. As a result, the country is facing a youth epidemic of e-cigarette use. The unregulated nicotine levels in both cigarettes and e-cigarettes can lead to repeated and overexposure of nicotine to youth which can lead to the addiction and detrimental effects on their cognitive functions. Over the past decade, the corrective measures being taken by the FDA for cigarette and e-cigarette regulations also should focus on nicotine exposure levels. Before it is too late to prevent youth from lifetime addiction to nicotine, it is important to address the issues of nicotine concentration, nicotine flux and the e-cigarette device regulations while offering adults with smoking disorder less harmful alternatives to cigarettes.